Electronic and Thermal Properties of Graphene - Rhee, Kyong Yop (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue includes recent research articles and extensive reviews on graphene-based next-generation electronics, bringing together perspectives from different branches of science and engineering. The papers presented in this volume cover experimental, computational and theoretical aspects of the electrical and thermal properties of graphene and its applications in batteries, electrodes, sensors and ferromagnetism. In addition, this Special Issue covers many important state-of-the-art technologies and methodologies regarding the synthesis, fabrication, characterization and applications of graphene-based nanocomposites.